2021
DOI: 10.3390/su13105390
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Circular Thinking in Consumer Purchase Intention to Buy Sustainable Waste-To-Value (WTV) Foods

Abstract: One of the new fronts in food research is related to waste reuse and the impact of by-products on food nutrition intensity. These foods are Waste-to-Value (WTV) products that are suitable for demonstrating the processes of the circular economy (CE), in which another excess material is converted into a new food, generating higher nutritional properties. The manifestation of customer reaction is very strong when buying these products. Consumer findings can strongly support or hinder the development of circular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 75 publications
(106 reference statements)
1
14
0
Order By: Relevance
“…When asked about their feeling and attitude upon hearing about valorising food waste as a novel food ingredient, more than half of the young adults answered, "strongly positive and positive (57%)" and "strongly acceptable and acceptable (62%)", respectively. The positive attitude of young adults towards sustainable food products in the present study was found to be in line with other studies, which reported younger consumers as the group who are actively looking for new sources of food and are concerned about sustainable food development (Vermeir and Verbeke, 2008;Pelletier et al, 2013;Kanchanapibul et al, 2014;Ali et al, 2021).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…When asked about their feeling and attitude upon hearing about valorising food waste as a novel food ingredient, more than half of the young adults answered, "strongly positive and positive (57%)" and "strongly acceptable and acceptable (62%)", respectively. The positive attitude of young adults towards sustainable food products in the present study was found to be in line with other studies, which reported younger consumers as the group who are actively looking for new sources of food and are concerned about sustainable food development (Vermeir and Verbeke, 2008;Pelletier et al, 2013;Kanchanapibul et al, 2014;Ali et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…The active engagement of young adults in sustainable development efforts is central to achieving sustainable, inclusive and stable societies (United Nations, 2018). The study by Ali et al (2021) suggested that consumers of the younger age group (18-35 years old) showed a greater preference to purchase sustainable products and may be viewed as consumers of the future. For the aforementioned reasons, young adults who were undergraduates at universities were selected as the target of interest in this study.…”
Section: Introductionmentioning
confidence: 99%
“…This nutritional concept of value‐added food may be more convincing for consumers than the marketing definition. There is a positive association between the nutritional value and purchasing intention of upcycled foods (Ali et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Upcycled foods use unmarketable ingredients generated during harvesting, processing and preparation, such as imperfect crops, by‐products and scraps from food preparation (The Upcycled Foods Definition Task Force, 2020) to produce new foods and contribute to the circular economy (Ali et al ., 2021). Upcycled food production returns wasted food to the supply chain to address sustainable food production and food waste management (Moshtaghian et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Older people are less inclined towards upcycled foods [60,61], but the comparison of different generations shows that middle-aged consumers, overall, have a lower acceptability of upcycled foods compared to younger and older generations [16]. It is worth mentioning that findings for sociodemographic factors are not consistent in all studies [22,60,66] and thus should be interpreted with caution, as the context of each study and the type of upcycled food under investigation were different.…”
Section: Consumer Sociodemographic Characteristics and Beliefsmentioning
confidence: 99%